Overview of approved and upcoming vaccines for SARS-CoV-2: a living review. Issue 1 (22nd May 2021) - Alderson, Jennifer; Batchelor, Vicky; O'Hanlon, Miriam; Cifuentes, Liliana; Richter, Felix Clemens; Kopycinski, Jakub
Abstract: The rapid design and implementation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccines is testament to a successfully coordinated global research effort. While employing a variety of different technologies, some of which have been used for the first time, all approved vaccines demonstrate high levels of efficacy with excellent safety profiles. Despite this, there remains an urgent global demand for coronavirus disease 2019 vaccines that require further candidates to pass phase 3 clinical trials. In the expectation of SARS-CoV-2 becoming endemic, researchers are looking to adjust the vaccine constructs to tackle emerging variants. In this review, we outline different platforms used for approved vaccines and summarize latest research data with regards to immunogenicity, dosing regimens and efficiency against emerging variants.